2020
DOI: 10.1080/02640414.2020.1725993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual, automatic and semiautomatic methods to determine ventilatory indices in 50 to 60 years old adults

Abstract: The aim of this study was to compare different methods of detecting ventilatory indices (VI) and to investigate the impact of cardiorespiratory fitness (CRF) level on VI detection. Fifty females and fifty males completed a graded exercise test until volitional exhaustion with continuous gas-exchange measurement. The first and second ventilatory indices (VI-1, VI-2) were detected through different single automatic methods and through a semiautomatic method which combines visual and automatic detection methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To determine AnT by detecting of RCP, i.e. VT2, we used visual methods, after polynomial regression analysis of trends in the dynamics of ventilatory variables: Ve, VCO 2 , VO 2 , values of Ve/VCO 2 , Ve/ VO 2 , and RER versus time [23,24]. According to Beaver et al [23] RCP cannot always be detected, which is also confirmed by the experience of Ekkekakis et al [25].…”
Section: Determination Of Ant By Rcpmentioning
confidence: 78%
See 1 more Smart Citation
“…To determine AnT by detecting of RCP, i.e. VT2, we used visual methods, after polynomial regression analysis of trends in the dynamics of ventilatory variables: Ve, VCO 2 , VO 2 , values of Ve/VCO 2 , Ve/ VO 2 , and RER versus time [23,24]. According to Beaver et al [23] RCP cannot always be detected, which is also confirmed by the experience of Ekkekakis et al [25].…”
Section: Determination Of Ant By Rcpmentioning
confidence: 78%
“…Santos & Giannella-Neto detected RCP in 88% of VO2max [32]. Pühringer et al detect VT2 at 83 ± 10% of VO 2peak [24].…”
Section: Discussionmentioning
confidence: 98%
“…Santos & Giannella-Neto found AnT at 88% of VO 2max (Santos, 2004). Pühringer et al found VT2 at 83 ± 10% of VO 2peak (Pühringer, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…The ventilatory indices POE, AT and RCP were determined semiautomatic by combining automatic and visual detection methods ( 34 ). First, the indices were determined automatically using polynomial regression.…”
Section: Methodsmentioning
confidence: 99%